2001
DOI: 10.1103/physrevlett.86.1235
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Mode Excitation in Electron Holes due to Wave Bounce Resonances

Abstract: A kinetic theory of resonant interaction between electrostatic waves and the bounce motion of electrostatically trapped electrons is developed. Precise criteria are derived for the stability of electrostatic potential structures which trap electrons in a highly magnetized plasma. The theory explains the energy transfer from electron phase space holes to waves observed in simulations. It may also account for the destabilization of electrostatic waves propagating obliquely to the geomagnetic field and some chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
(38 reference statements)
6
30
0
Order By: Relevance
“…[13][14][15][16] Lastly there are miscellaneous explorations of the behavior of 1D phase-space vortices ͑"holes"͒ and the like. [17][18][19][20][21][22][23] For historical completeness one should also note a particular laboratory experiment done in a Q-machine resulting in the creation of a single KEEN-like cell rather than in a long wave train. 24 There is also a recent publication by Valentini et al 25 which bears directly on the kind of work presented in this publication.…”
Section: Related Previous Workmentioning
confidence: 99%
“…[13][14][15][16] Lastly there are miscellaneous explorations of the behavior of 1D phase-space vortices ͑"holes"͒ and the like. [17][18][19][20][21][22][23] For historical completeness one should also note a particular laboratory experiment done in a Q-machine resulting in the creation of a single KEEN-like cell rather than in a long wave train. 24 There is also a recent publication by Valentini et al 25 which bears directly on the kind of work presented in this publication.…”
Section: Related Previous Workmentioning
confidence: 99%
“…Their equilibrium is intrinsically kinetic, in that they are accompanied by a stationary hole in the electron distribution function. DOI Among several physical processes accompanying the wave-plasma interaction, particular interest has been devoted to electron and ion holes in phase space [1][2][3][4][5], which are typical nonlinear kinetic structures producing macroscopic measurable effects in space plasmas [6][7][8][9]. The use of kinetic codes makes it possible to investigate at once both the hydrodynamic and the kinetic aspects of the waveplasma interaction [10 -15].…”
mentioning
confidence: 99%
“…Krasovsky et al [10] showed theoretically and by computer simulations that the electron holes perform inelastic collisions. Vetoulis and Oppenheim [11] studied the radiation generation due to bounce resonances in electron holes. Guio et al [12,13] investigated numerically the dynamics of phase-space vortices in a collisionless plasma, as well as the generation of phase-space structures by an obstacle in a streaming plasma.…”
Section: Introductionmentioning
confidence: 99%